MODELING OF COMMUNICATION PROCESSES ON THE WEBSITE FOR HR-CONSULTING - SHILINH, ANNA; PASKO, ANASTASIIA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
В роботі запропоновано моделювання комунікаційних процесів веб-сайту для HR-консалтингу. Запропоновано інформаційну модель комунікаційного циклу між користувачами сайту, яка представлена за допомогою ER-діаграми, та функціональну модель замовлення послуги на сайті для HR-консалтингу за допомогою DFD діаграми. Результати дослідження використовуються і можуть бути використані для розробки та ефективної роботи відповідного веб-сайту.  For both business and personal development, it is important to define the specifics of recruitment. This process involves users who need information about various professional opportunities and businesses that operate in the modern labor market. Therefore, the task is to combine all the links in the recruitment process. Today, HR consulting has effective tools for achieving this goal. In this dynamic context, developing an effective website is a key condition for achieving a competitive advantage. An important stage of this organization is the communication process of consulting participants. That is why this paper presents a conceptual model of the communication cycle using an Entity-Relationship Diagram. This Entity-Relationship Diagram includes the User, Message, Manager, and Response tables, which contain the corresponding attributes and relationships. The functional model of ordering a service on a website for HR consulting is presented in the paper with the relevant Data Flow Diagram and a detailed diagram of the manager's processing functioning to the corresponding questionnaire filled out by the user on the website. In particular, the Data Flow Diagram is used to visualize the interaction of the main modules of the communication process, such as the User and the Manager, and focuses on the dynamic aspects of the system. A more detailed description of the process of processing a questionnaire through an HR consulting website is described in the corresponding detailed diagram. The use of Entity-Relationship Diagram and Data Flow Diagram allowed us to show the communication process between users in more detail, which contributes to more efficient system design and development.
Keywords: communication process; HR consulting; website; information model; functional model